Thermal performance analysis of Al2O3/R-134a nanorefrigerant - Mahbubul, I.M.; Saadah, A.; Saidur, R.; Khairul, M.A.; Kamyar, A. (Elsevier, 2015)
Nowadays, nanofluids are being considered as an efficient heat transfer fluid in various thermal applications. Refrigerant-based nanofluids, termed as "nanorefrigerants", have the potential to improve the heat transfer performances of refrigeration and air-conditioning systems. This study analyzed the thermophysical properties and their effects on the coefficient of performance (COP) resulted by addition of 5 vol. Al2O3 nanoparticles into R-134a refrigerant at temperatures of 283-308 K. The analysis has been done for a uniform mass flux through a horizontal smooth tube using established correlations. The results indicate that the thermal conductivity, dynamic viscosity, and density of Al2O3/R-134a nanorefrigerant increased about 28.58, 13.68, and 11, respectively compared to the base refrigerant (R-134a) for the same temperature. On the other hand, specific heat of nanorefrigerant is slightly lower than that of R-134a. Moreover, Al2O3/R-134a nanorefrigerant shows the highest COP of 15, 3.2, and 2.6 for thermal conductivity, density, and specific heat, respectively compared to R-134a refrigerant. Therefore, application of nanoparticles in refrigeration and air-conditioning systems is promising to improve the performances of the systems. (C) 2015 Elsevier Ltd. All rights reserved.